THE EFFECT OF FINANCIAL INCLUSION THROUGH CREDIT ACCESS ON HOUSEHOLD WELFARE IN INDONESIA - Shafyra Amani; Sulthan Faiz Akbar; Hasna Rofifah; Olivia Christine Angelina; Akthia Lazzuar Mantari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Financial inclusion is widely promoted as a program for enhancing household welfare by expanding access to credit and other financial services. This study empirically examines the impact of credit access on household welfare in Indonesia, utilizing total and disaggregated expenditures as indicators of welfare. Drawing on data from the fifth wave of the Indonesia Family Life Survey (IFLS 5, 2014-2015), we implement a quasi experimental design with Propensity Score Matching (PSM) to compare households that received individual credit with observationally similar control households. The results reveal that credit access has a significant impact on nonfood expenditures, while food expenditures remain unaffected. These findings are consistent with Amartya Sen's capability framework, which emphasizes the importance of inclusive financial access in expanding individual freedoms, and with Engel's Law, which predicts that households allocate additional income toward quality-enhancing goods once their basic food needs are met. Our study highlights the role of targeted credit provision in promoting welfare beyond subsistence consumption, offering policy insights for strengthening inclusive finance initiatives in developing economies.